Socio-Affective Strategy Towards Students’ Self-Esteem in Speaking Ability - Krismona Ayu Widyaningrum; Elysa Hartati (Yayasan Karinosseff Muda Indonesia, 2023)
This study aimed to find out the use of Socio-Affective Strategy towards students' self-esteem in speaking ability. This study was carried out at one of the Junior High School, located in Pakem, Sleman Regency, Special Region of Yogyakarta. This research used mix method combining two kind of researches, quantitative and qualitative. The participants of this research were one class from several classes in the junior high school the academic year 2022/2023 with a total of 32 students. The instruments used to conduct the data for this study were observation, questionnaires and in-depth interview. The results of this study indicated that many students still believe their speaking abilities need improvement, but this does not cause them to feel less than they are. This means that many students have high self-esteem, but there are still some students who have low self-esteem. The teachers' opinion about Socio-Affective Strategy has been confirmed by the survey which shows that by discussing with friends and in groups, it can increase students' courage and confidence, especially when speaking in English. This research gives insight to the field of language education by activating the Socio-Affective Strategy in fostering the students’ self-esteem in speaking skill.